To help you out I save your picture and explain the process. The only thing tht confuses me is problem #!6. But I hope I helped you out in the slightest bit
Given:
The sum of two terms of GP is 6 and that of first four terms is ![\dfrac{15}{2}.](https://tex.z-dn.net/?f=%5Cdfrac%7B15%7D%7B2%7D.)
To find:
The sum of first six terms.
Solution:
We have,
![S_2=6](https://tex.z-dn.net/?f=S_2%3D6)
![S_4=\dfrac{15}{2}](https://tex.z-dn.net/?f=S_4%3D%5Cdfrac%7B15%7D%7B2%7D)
Sum of first n terms of a GP is
...(i)
Putting n=2, we get
![S_2=\dfrac{a(1-r^2)}{1-r}](https://tex.z-dn.net/?f=S_2%3D%5Cdfrac%7Ba%281-r%5E2%29%7D%7B1-r%7D)
![6=\dfrac{a(1-r)(1+r)}{1-r}](https://tex.z-dn.net/?f=6%3D%5Cdfrac%7Ba%281-r%29%281%2Br%29%7D%7B1-r%7D)
...(ii)
Putting n=4, we get
![S_4=\dfrac{a(1-r^4)}{1-r}](https://tex.z-dn.net/?f=S_4%3D%5Cdfrac%7Ba%281-r%5E4%29%7D%7B1-r%7D)
![\dfrac{15}{2}=\dfrac{a(1-r^2)(1+r^2)}{1-r}](https://tex.z-dn.net/?f=%5Cdfrac%7B15%7D%7B2%7D%3D%5Cdfrac%7Ba%281-r%5E2%29%281%2Br%5E2%29%7D%7B1-r%7D)
![\dfrac{15}{2}=\dfrac{a(1+r)(1-r)(1+r^2)}{1-r}](https://tex.z-dn.net/?f=%5Cdfrac%7B15%7D%7B2%7D%3D%5Cdfrac%7Ba%281%2Br%29%281-r%29%281%2Br%5E2%29%7D%7B1-r%7D)
(Using (ii))
Divide both sides by 6.
Taking square root on both sides, we get
![\pm 0.5=r](https://tex.z-dn.net/?f=%5Cpm%200.5%3Dr)
Case 1: If r is positive, then using (ii) we get
The sum of first 6 terms is
![S_6=\dfrac{4(1-(0.5)^6)}{(1-0.5)}](https://tex.z-dn.net/?f=S_6%3D%5Cdfrac%7B4%281-%280.5%29%5E6%29%7D%7B%281-0.5%29%7D)
![S_6=\dfrac{4(1-0.015625)}{0.5}](https://tex.z-dn.net/?f=S_6%3D%5Cdfrac%7B4%281-0.015625%29%7D%7B0.5%7D)
![S_6=8(0.984375)](https://tex.z-dn.net/?f=S_6%3D8%280.984375%29)
![S_6=7.875](https://tex.z-dn.net/?f=S_6%3D7.875)
Case 2: If r is negative, then using (ii) we get
The sum of first 6 terms is
![S_6=\dfrac{12(1-(-0.5)^6)}{(1+0.5)}](https://tex.z-dn.net/?f=S_6%3D%5Cdfrac%7B12%281-%28-0.5%29%5E6%29%7D%7B%281%2B0.5%29%7D)
![S_6=\dfrac{12(1-0.015625)}{1.5}](https://tex.z-dn.net/?f=S_6%3D%5Cdfrac%7B12%281-0.015625%29%7D%7B1.5%7D)
![S_6=8(0.984375)](https://tex.z-dn.net/?f=S_6%3D8%280.984375%29)
![S_6=7.875](https://tex.z-dn.net/?f=S_6%3D7.875)
Therefore, the sum of the first six terms is 7.875.
Answer:
6.9 foot.
Step-by-step explanation:
Given: Length of lamp post= 12-foot.
The angle of elevation of the sun is 60°.
∴ The length of Lamp post, which is opposite is 12-foot.
Now, finding the length of shadow cast by foot lamp.
Length of shadow is adjacent.
∴ We know the formula for
= ![\frac{Opposite}{adjacent}](https://tex.z-dn.net/?f=%5Cfrac%7BOpposite%7D%7Badjacent%7D)
Next, putting the value in the formula.
⇒ ![Tan 60° = \frac{12}{adjacent}](https://tex.z-dn.net/?f=Tan%2060%C2%B0%20%3D%20%5Cfrac%7B12%7D%7Badjacent%7D)
Cross multiplying both side and using the value of Tan 60°
∴ Adjacent=
≅ 6.9 (nearest tenth value)
6.9 is the length of shadow cast by a 12-foot lamp post.
The expression of X in terms of l is X = √5 l
<h3>How to calculate the diagonal of a rectangle</h3>
According to the given information:
- Length = w
- If length<u> l is twice as long </u>as the width, then l = 2w
Determine the diagonal using the Pythagoras theorem:
X² = w²+(2w)²
X² = w² + 4w²
X =√5w²
X = √5 w
Replace w with l
X = √5 l
Hence the expression of X in terms of l is X = √5 l
Learn more on diagonals here: brainly.com/question/26154016
Answer:
7p−q−12
Step-by-step explanation: